Pengukuran Kinerja Persediaan di Gudang Bahan Baku Menggunakan Turn Over Ratio (TOR) pada Industri Manufaktur - M Hudori (Politeknik Kelapa Sawit Citra Widya Edukasi, 2017)
A company must strive to achieve its goal of creating and maintaining its customers, in the midst of intense business competition. In order to achieve these objectives, the company must meet customer needs in a timely manner in accordance with the wishes of the customer, so that required supplies of goods sufficient to meet those needs. Inventory turnover is a inventory performance indicator. Measurement of performance is done by calculating the turnover ratio of goods (TOR). The purpose of this study is to determine the performance of raw material inventory in the warehouse through the calculation of turnover ratio (TOR). The research was conducted at a manufacturing company, a company producing carton for packaging consumer products, located in Bekasi District. The object of research is the raw material used to make carton packaging, which is as much as 18 (eighteen) types. The data used are initial inventory status data, raw material data entering warehouse and raw material usage for three months (January - March 2017). The results showed that the performance of raw material inventory in the company is very low. This can be seen from the cumulative TOR value for three months (January - March 2017), which only ranged from 0.10 to 4.88 times. While the length of raw material inventory time ranges from 13.11 to 649.45 days.